The Performance of Savonius Windmill With Guide Vane - Sugiharto, Budi (Sekolah Tinggi Teknologi Adisutjipto, 2018)
This paper aims to observed the performance of Savonius windmills with 16 guide vanes with variations in the guide vane angle of 30 °, 45 ° and 60 °. Tests are carried out openly with the help of a fan as a source of air flow. The best performance results obtained at wind speeds of 5 m / s, namely the highest power coefficient occurs on the mill with a 45 ° angled guide vane of 24%. The highest torque coefficient is owned by a windmill with a 45 ° angular guide vane of 20% at a rotational speed of 100 rpm.